Kapitał społeczny młodzieży jako podstawa socjalizacji politycznej oraz rozwoju społeczeństwa obywatelskiego – sprawozdanie z badań niemieckich - Hildebrandt-Wypych, Dobrochna (Wydawnictwo Naukowe UAM, 2012)
The paper explores the influence of different aspects of youth's social capital on political attitudes and behavour among German youth. The influence of various aspects of adolescent's and elary adult's social capital (e.g. social networks) on political socialization was recently analyzed by Julia Schafer on the basis of seven German youth studies (incl. Shell Youth Studies and DJI Youth Surveys). The presentation of the main research findings is preceded by a brief introduction into the area of social capital research, as well as the social and structural determinants of social capital among German youth, including the continuous influence of the East-West divide on the outcomes of their political socialization.
Keywords: social capital; political socialization; civic society; German research